Implementation of International Safety Standard EN ISO 13849 into Machinery of Tyre Industry - Wongpiriyayothar, N.; Chitwong, S. (My University, 2017)
This paper presents application of international safety standard in risk assessment and risk reduction following by machinery directive. Many industries using machinery for manufacturing products have tendency to take risk from poor-quality of machinery design which may not be produced according to international safety standard. This can lead dangerous situation to machine user. The new standard EN ISO 13849-1 [1] which replaced the old standard EN 954-1 [2] definitely in December 2011 made machine designer not be familiar with the new concept and feel confused due to most of concerned parameters shown in term of statistic value that there are difficulty in interpretation and understanding. In the present, there is still lack of examples of implementation this standard into machinery of specific industry, especially in tyre industry. Therefore the objective of this paper is made for implementation this safety standard into machinery of tyre industry in order to build a safe situation for machine user.
Keywords: Common Cause Failure (CCF); Diagnostic Coverage (DC); Mean Time to Dangerous Failure (MTTFd); Performance Level (PL); Safety-Related Parts of Control System (SRP/CS)